Separation of Soluble Benzene from an Aqueous Solution by Pervaporation Using a Commercial Polydimethylsiloxane Membrane - Salam H. Rasheed; Salah S. Ibrahim; Qusay F. Alsalhy; Issam K. Salih (Membranes, 2022)
A developed polydimethylsiloxane (PDMS) membrane was used to separate soluble benzene compounds (C6H6) from an aqueous solution via a pervaporation (PV) process. This membrane was characterized by scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, contact angle (CA), and energy-dispersive spectroscopy (EDS). To evaluate the performance of the membrane, the separation factor and permeation flux were estimated in various operating conditions, including the feed temperature, initial benzene concentration, and feed flow rate. The experiments to maximize the separation factor and permeation flux were designed using the response surface method (RSM) that is built into Minitab 18. A quadratic model (nonlinear regression equation) was suggested to obtain mathematical expressions to predict the benzene permeation flux and the separation factor according to the effect of the parameters’ interaction. The optimization of the PV was performed using an RSM that was based on the analysis of variance (ANOVA). The optimal values of the benzene permeation flux and separation factor were 6.7 g/m2·h and 39.8, respectively, at the optimal conditions of temperature (30 °C), initial concentration of benzene (1000 ppm), and feed flow rate (3.5 L/min). It was found that the feed concentration was the most influential parameter, leading to a significant increase in the permeation flux and separation factor of the PDMS membrane.